Decontamination interventions for the reuse of surgical mask personal protective equipment: a systematic review. Issue 2 (October 2020) - Zorko, D.J.; Gertsman, S.; O'Hearn, K.; Timmerman, N.; Ambu-Ali, N.; Dinh, T.; Sampson, M.; Sikora, L.; McNally, J.D.; Choong, K.
SUMMARY: Background: The high demand for personal protective equipment during the novel coronavirus outbreak has prompted the need to develop strategies to conserve supply. Little is known regarding decontamination interventions to allow for surgical mask reuse. Aim: To identify and synthesize data from original research evaluating interventions to decontaminate surgical masks for the purpose of reuse. Methods: MEDLINE, Embase, CENTRAL, Global Health, the WHO COVID-19 database, Google Scholar, DisasterLit, preprint servers, and prominent journals from inception to April 8 th, 2020, were searched for prospective original research on decontamination interventions for surgical masks. Citation screening was conducted independently in duplicate. Study characteristics, interventions, and outcomes were extracted from included studies by two independent reviewers. Outcomes of interest included impact of decontamination interventions on surgical mask performance and germicidal effects. Findings: Seven studies met eligibility criteria: one evaluated the effects of heat and chemical interventions applied after mask use on mask performance, and six evaluated interventions applied prior to mask use to enhance antimicrobial properties and/or mask performance. Mask performance and germicidal effects were evaluated with heterogeneous test conditions. Safety outcomes were infrequently evaluated. Mask performance was best preserved with dry heat decontamination. Good germicidal effects were observed in salt-, N-halamine-, and nanoparticle-coated masks. Conclusion: There is limited evidence on the safety or efficacy of surgical mask decontamination. Given the heterogeneous methods used in studies to date, we are unable to draw conclusions on the most efficacious and safe intervention for decontaminating surgical masks.